2021
DOI: 10.30572/2018/kje/110105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crab Shell and Charcoal Reinforcements on the Mechanical Properties of Polyester Matrix Composites

Abstract: Composites are produced when two or more materials are used to give combination of properties that cannot be attained otherwise. This study aims to use crab shell and charcoal reinforcements to enhance the mechanical properties of polyester composites and decrease the environmental pollution caused by the agro waste. In this study, 5 – 25 wt. % of 100 g of grounded charcoal and crab shell with an average particles size of 150 µm were used for polyester matrix composites. Flexural strength, impact resistance, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…This implies that these factors negatively affected the FS. This finding agreed with Bolasodun et al [45] who concluded that the FS of polyester matrix composites decreased with increasing the crab and charcoal content up to 10 wt% due to poor dispersion of the particulates in the matrix resulting in weak bonding. This result is consistent with the microscopy images of the WPC surfaces as shown in Table 11.…”
Section: Effects Of Composition and Optimizing The Flexural Propertiessupporting
confidence: 92%
See 2 more Smart Citations
“…This implies that these factors negatively affected the FS. This finding agreed with Bolasodun et al [45] who concluded that the FS of polyester matrix composites decreased with increasing the crab and charcoal content up to 10 wt% due to poor dispersion of the particulates in the matrix resulting in weak bonding. This result is consistent with the microscopy images of the WPC surfaces as shown in Table 11.…”
Section: Effects Of Composition and Optimizing The Flexural Propertiessupporting
confidence: 92%
“…The result observed that the addition of the CS into the hybrid WPCs led to a decrease in the hardness properties. This is consistent with Bolasodun et al [45] who reported that when the crab shell particles ranging from 5 to 10 wt% were used for reinforcement, the hardness properties of the composites decreased due to the agglomeration of the particulates in the matrix. The surface plot of the output response for the hardness properties is presented in Fig.…”
Section: Effects Of Composition and Optimizing The Hardness Valuessupporting
confidence: 91%
See 1 more Smart Citation